Listening habits and subjective effects of background music in young adults with and without ADHD - Lachance, Kelly-Ann; Pelland-Goulet, Pénélope; Gosselin, Nathalie (Frontiers in Psychology, 2025)
Adults listen to an average of 20.7 hours of music per week, according to a study conducted across 26 countries. Numerous studies indicate that listening to music can have beneficial effects on cognitive performance and emotional well-being. Music listening habits may vary depending on individual needs and listening contexts. However, a limited number of studies have specifically examined the patterns of background music usage during various more or less cognitive activities, especially among individuals with attentional difficulties related to ADHD. This study primarily aimed to compare music listening habits during daily activities that are more and less cognitive (e.g., studying, problem-solving versus cleaning, engaging in sports) between neurotypical young adults and those screened for ADHD (respondents who were identified as likely having ADHD based on the number of self-reported symptoms). To achieve this, 434 young adults aged 17 to 30 responded to an online survey. The results indicate that certain listening habits differ significantly between the neurotypical and ADHD-screened groups. The ADHD-screened group reports significantly more background music listening during less cognitive activities and while studying, compared to the neurotypical group. The results also reveal a difference in the proportion of individuals preferring stimulating music between the groups: ADHD-screened individuals report significantly more frequent listening to stimulating music, regardless of the activity type (more or less cognitive). Other aspects of music listening are common to both groups. Regardless of the group, more respondents reported preferring to listen to relaxing, instrumental, familiar and self-chosen music during more cognitive activities, whereas for less cognitive activities, more individuals mentioned preferring to listen to music that is stimulating, with lyrics, familiar and self-chosen. Overall, the results confirm that most young adults listen to music during their daily activities and perceive positive effects from this listening.